Izzivi in dileme osmišljene uporabe IKT pri pouku - Lipovec, Alenka; Krašna, Marjan; Pesek, Igor (2019)
Challenges and dilemmas of the conceptualized ICT use in teaching. The goal of the PIKT.UM project was to equip (future) teachers with skills and knowledge of flexible teaching approaches that involve meaningful use of ICT. By critically assessing the choice and use of both, didactical approaches and ICT tools, we wanted to enable the increase in educational use of modern technology. A monograph serves the similar goal as the project, namely to provide a list of skills and knowledge that a teacher should have regarding the meaningful conceptual use of ICTs. The added value of the contributions in monograph is an interweaving of a mechanistic approach to ICT through tools and a didactic approach through innovative forms of learning and teaching. Experts from all fields, from art to science, offer theoretical framework, research based findings and practical lessons for introducing ICT into school practice. The main message of the entire monograph is that the technology can be a powerful teaching tool, which should be treated with care and in accordance with the goals of education.
Keywords: innovative learning environments; conceptual use of ICT; pedagogical content knowledge; European digital competence framework for teachers; students’ centered teaching